Experimental reference stress techniques for the prediction of creep deformation using lead alloy models - Hyde, T.H. (1976)
It is necessary at the design stage to predict the creep behaviour of components and structures operating at high temperature. The direct calculation of the creep behaviour requires extensive material data for the long service lives of the components and engineering methods are needed to minimise the amount of data needed. This can be achieved in some cases by use of the so called Reference stress method and the objective of this work was the experimental prediction of the creep deformation of some components using developments of this idea. It has been achieved by the determination of Reference stresses from accelerated room temperature creep tests of lead alloy models.